Economic Evaluation of Digital Health Interventions in Palliative Care: A Systematic Review of the Literature - Panagiota Naoum; Elpida Pavi; Kostas Athanasakis (Frontiers Media S.A., 2021)
Introduction: Digital health interventions can facilitate the provision of palliative care. However, the economic evaluation of such interventions has not yet been a standard practice. The present study aimed to identify the existing literature on the particular subject.Methods: A systematic search was conducted in six literature databases between 2010 and 2021: PubMed, Scopus, DARE, NHS EED, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials. Methodological quality was assessed with the Drummond Checklist.Results: The search identified 423 publications, 66 of which were removed as duplicates, resulting in 357 records to be screened by title and abstract. Ten studies were subjected to full-text review and 3 were included in the analysis. The interventions of these studies referred to video consultations and eHealth interventions for symptom management. Overall, the digital health interventions incurred lower costs compared with usual care or no intervention and were considered cost saving and cost-effective. The methodological quality of the studies was considered good.Conclusion: The results of this systematic review indicate that the use of digital health interventions has the potential to be cost-effective in palliative care. However, applicability and generalizability of the evidence is uncertain, mainly due to methodological heterogeneity and scarcity of research.